2021
DOI: 10.1155/2021/7029130
|View full text |Cite
|
Sign up to set email alerts
|

Screening Hub Genes of Hepatocellular Carcinoma Based on Public Databases

Abstract: Tumor recurrence and metastasis often occur in HCC patients after surgery, and the prognosis is not optimistic. Hence, searching effective biomarkers for prognosis of is of great importance. Firstly, HCC-related data was acquired from the TCGA and GEO databases. Based on GEO data, 256 differentially expressed genes (DEGs) were obtained firstly. Subsequently, to clarify function of DEGs, clusterProfiler package was used to conduct functional enrichment analyses on DEGs. Protein-protein interaction (PPI) network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…LIHC patients had an overabundance of Orthohepadnavirus (HBV genus), which is a major causative etiological factor. Overall, 13 consistent hub genes identified by our work and recent studies [15][16][17] were confirmed to be associated with HBV infection (Figure S1A, Table S1). Our gene set overrepresentation analysis using gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) revealed that genes associated with the HBV genus were enriched in biological pathways like mitotic nuclear division, cell cycle, DNA replication, chromosome segregation and nuclear division, which were also consistent with previously identified pathways that may contribute to the pathogenesis of HBV-infected liver cancer (Figure S1A) 17 .…”
Section: Validating Known Associations On Pathogenic Infectionssupporting
confidence: 85%
“…LIHC patients had an overabundance of Orthohepadnavirus (HBV genus), which is a major causative etiological factor. Overall, 13 consistent hub genes identified by our work and recent studies [15][16][17] were confirmed to be associated with HBV infection (Figure S1A, Table S1). Our gene set overrepresentation analysis using gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) revealed that genes associated with the HBV genus were enriched in biological pathways like mitotic nuclear division, cell cycle, DNA replication, chromosome segregation and nuclear division, which were also consistent with previously identified pathways that may contribute to the pathogenesis of HBV-infected liver cancer (Figure S1A) 17 .…”
Section: Validating Known Associations On Pathogenic Infectionssupporting
confidence: 85%
“…A gene with a absolute value of log 2 (fold change) ≥ 1 through the limma package [17][18][19] and SMD < 0 was identified as having low-expression genes (LEGs) in SCLC. A gene that was positively related to ITGAV expression (Pearson coefficient ≥ 0.3, p < 0.05) in > 30% (4/12) datasets was considered as ITGAV-positivelyrelated genes (ITGAV-PRGs).…”
Section: The Underlying Mechanisms Resulting In Low-itgav Expression ...mentioning
confidence: 99%
“…KIF2C resulted in tumorigenesis due to abnormal cell cycle progression and metastasis in cervical cancer (Yang et al, 2022). In case of HCC, it participated in the progression of HCC and could be a potential therapeutic target (Gao et al, 2021). On the other hand, in case of GBM, it had missense mutations at three different locations on phosphorylation, ubiquitination, acetylation, and methylation PTM sites with diploid and gain copy number alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a complex disease caused due to uncontrolled division and growth of cells, categorized according to the progression in organs such as breast cancer, blood cancer, colon cancer, liver cancer, etc. Liver cancer, also known as hepatocellular carcinoma (HCC), has nowadays become a common cancer type, with approximately 830000 deaths in 2020 alone ( Gao et al, 2021). Tumorigenesis or transformation of normal cells into cancerous cells often results in uncontrolled cell proliferation, metastasis, and apoptosis evasion (Cao, 2017).…”
Section: Introductionmentioning
confidence: 99%